The use of magical plants by curanderos in the Ecuador highlands - Albán Manuel; Cavender Anthony P (BMC, 2009)
Abstract Although the use of plants for treating supernaturally caused illnesses (e.g., soul loss, evil wind, witchcraft) has been documented in the Ecuador highlands, so-called magical plants have received much less focused attention than plants used for treating naturalistic disorders. Drawing on interviews done in 2002 and 2003 with 116 curanderos residing in the Ecuador highlands, this paper examines the characteristics of plants identified as magical, how they are used, and how the study of magical plants provides insights into the mindscape of residents of the highlands.